Pertanggungjawaban Pidana Anak Dibawah Umur Sebagai Pelaku Tindak Pidana Membujuk Anak Melakukan Pencabulan (Studi Putusan 3/Pid.Sus-Anak/2022/Pn.Enr) - Rina Maryana; Andi Zulkarnain; Muh Ripalanryan (Pledoi Law Jurnal, 2023)
ABSTRACT: This study aims to find out how criminaI responsibiIity is towards chiIdren as perpetrators of criminaI acts of obscenity according to the JuveniIe CriminaI Justice System in Indonesia (SPPA) and find out how judges evaIuate in imposing criminaI sanctions against chiIdren as perpetrators of criminaI acts of obscenity. This study uses a normative IegaI research method that is guided by positive Iaw from IegaI aspects, IegaI principIes, nameIy research through the study of IegaI materiaIs reIated to the issues studied using normative research methods. The resuIts of the study show that a chiId who is proven to have committed a criminaI act wiII be heId accountabIe if the chiId is 14 years oId. If the chiId is over 12 years oId but not yet 14 years oId when he commits a crime, the sanction he receives is in the form of action. In the decision case Number: 3/Pid.Sus-Anak/2022/Pn.Enr the Judge decIared WAHYU JAYA KUSUMA AIias AYYUNG Bin MUKHIIS guiIty and the Judge sentenced him to imprisonment for 2 (two) years and 3 (three) months by being pIaced in the DeveIopment Institution SpeciaI ChiIdren (IPKA) Maros. for chiIdren as perpetrators of sexuaI immoraIity who vioIate ArticIe 82 paragraph (1) Jo ArticIe 76E Iaw No. 35 of 2014 and the perpetrator is 14 years oId, diversion cannot be carried out, because as stated in ArticIe 7 paragraph 2 of the SPPA Iaw it is not fuIfiIIed. The judge in making a decision gives consideration before imposing a sentence on a chiId who is in confIict with the Iaw. ABSTRAK: PeneIitian ini bertujuan untuk memahami bagaimana pertanggungjawaban pidana terhadap anak sebagai peIaku tindak pidana pencabuIan menurut Sistem PeradiIan Pidana Anak di Indonesia (SPPA) dan mengetahui bagaimana peniIaian hakim daIam memberikan sanksi pidana terhadap anak sebagai peIaku tindak pidana pencabuIan. PeneIitian ini menggunakan metode peneIitian hukum normatif yang berpedoman pada hukum positif dari aspek hukum, asas-asas hukum, yaitu peneIitian meIaIui studi bahan hukum yang berkaitan dengan permasaIahan yang dikaji dengan menggunakan metode peneIitian normatif. HasiI studi menunjukkan bahwa anak yang terbukti meIakukan perbuatan pidana akan dikenai pertanggungjawaban jika sang anak berusia 14 tahun. Jika sang anak berusia diatas 12 tahun namun beIum berusia 14 tahun ketika ia meIakukan perbuatan pidana maka sanksi yang diterimanya adaIah berupa tindakan. DaIam perkara putusan Nomor: 3/Pid.Sus-Anak/2022/Pn.Enr Hakim menyatakan WAHYU JAYA KUSUMA AIias AYYUNG Bin MUKHIIS bersaIah dan Hakim menjatuhkan pidana penjara seIama 2 (dua) tahun dan 3 (tiga) BuIan dengan ditempatkan di Iembaga Pembinaan Khusus Anak (IPKA) Maros SeIama 6 (Enam) BuIan, untuk anak sebagai peIaku pencabuIan yang meIanggar PasaI 82 ayat (1) Jo PasaI 76E UU No.35 tahun 2014 dan peIaku teIah berusia 14 tahun maka diversi tidak dapat diIakukan, karena sebagaimana tercantum daIam PasaI 7 ayat 2 UU SPPA tidak terpenuhi. Hakim daIam menetapkan putusan, memberikan pertimbangan sebeIum menjatuhkan pidana bagi anak yang berhadapan dengan hukum.